KARAKTERISTIK DAN PERKEMBANGAN HARGA KAMBING KURBAN MENJELANG HARI RAYA IDUL ADHA DI KABUPATEN SEMARANG: CHARACTERISTICS AND PRICE DEVELOPMENT OF QURBANI GOAT APPROACHING EID AL-ADHA IN SEMARANG REGENCY - Edy Rianto; Brilliant Pranayudha Gemilang; Nangimul Huda; Endang Purbowati (Tropical Animal Science, 2026)
The characteristics and price of qurbani goats before Eid al-Adha (EA) needs to be known as a guideline for farmers/traders in providing qurbani goats and the right time to buy sacrificial goats. The material is goats sold as qurbani animals in Semarang regency. The study used a survey method with purposive sampling based on goats that had been sold. The parameters observed were goat breed, body weight (BW), body measurements and goat prices from the 23rd to the 1st day before EA. The results showed that the goats purchased were mostly Jawarandu breed (96.7%), male, horned black and white body color combination (33.3%), an average body weight of 40.6 kg, chest circumference of 76.8 cm, body length of 68.2 cm, shoulder height of 70.9 cm, aged between 1-1.5 years, and an average price of Rp. 3,000,000 to Rp. 4,000,000 per head. The results of the correlation regression analysis showed that the relationship between the price of qurbani goats per head and the time before EA followed the equation y = 26,071x + 4,000,000, with an r value = 0.204 (low). The relationship between the price of goats per head and BW followed the equation y = 79,565x + 349,252 with an r value = 0.848 (very strong). The relationship between the price of goats per kg and the time before EA followed the equation y = 932.77x + 96,955 with an r value = 0.575 (moderate). The relationship between goat price per kg and BW followed the equation y = -313.31x + 101,636 with a value of r = 0.263 (low). The conclusion of the was study that the purchase of sacrificial goats were male Jawarandu breed, horned, weighing 40.6 kg, aged 1-1.5 years, and priced at Rp. 3,000,000 to Rp. 4,000,000 per head. The price of goat per head was more influenced by the weight of the goat than the time leading up to the EA, while the price of the goat per kg was more influenced by the time leading up to the EA than the weight of the goat.